Methodology of the first combined in-flight and ex situ stability assessment of organic-based solar cells for space applications. Issue 13 (18th June 2018) - Schreurs, Dieter; Nagels, Steven; Cardinaletti, Ilaria; Vangerven, Tim; Cornelissen, Rob; Vodnik, Jelle; Hruby, Jaroslav; Deferme, Wim; Manca, Jean V.
Abstract: Abstract : One of the key aims of the OSCAR project (Optical Sensors based on CARbon-materials)—in the framework of the REXUS/BEXUS program—was to explore the use of organic-based solar cells for (aero)space applications through the in-flight investigation of devices' performance during a stratospheric balloon flight. Next to the in-flight experiments, complementary lab stability assessment tests were performed. In this contribution, both the in-flight and lab experimental methodology and the corresponding technical aspects will be discussed in detail. Furthermore, attention will be paid to the issues of packaging and radiation. The importance of the OSCAR-balloon experiment is not only that it has demonstrated for the first time the use of organic-based solar cells in (aero)space conditions but also that it can be considered as the pioneering start of specific stability assessment methodologies for organic-based solar cells for (aero)space applications.